2009
DOI: 10.1177/1756283x09346794
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection with ligation using a multi-band mucosectomy system in Barrett’s esophagus with high-grade dysplasia and intramucosal carcinoma

Abstract: Abstract:Background: Endoscopic therapy for early neoplasia in Barrett's esophagus (BE) is evolving. Endoscopic resection has an increasing role. We wanted to evaluate the safety and efficacy of multi-band ligation/resection [ER-L] without pre-injection in BE with high-grade dysplasia [HGD] and intramucosal carcinoma [IMCA]. Methods: A cohort of 65 consecutive patients from a single academic medical center, who underwent ER-L as part of endoscopic eradication therapy for BE with HGD/IMCA were studied. ER-L wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
17
0
2
Order By: Relevance
“…Recently, the OTSC device has been used in an animal model to perform full-thickness resection in the colon by using a clip-and-cut technique, 36 similar to the band ligation and cut technique used for EMR 37 and resection of subepithelial lesions. 38 In one of our patients, we resected a subepithelial lesion in a similar fashion, and deeper lesions may be resectable with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the OTSC device has been used in an animal model to perform full-thickness resection in the colon by using a clip-and-cut technique, 36 similar to the band ligation and cut technique used for EMR 37 and resection of subepithelial lesions. 38 In one of our patients, we resected a subepithelial lesion in a similar fashion, and deeper lesions may be resectable with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, MBM was compared with EMR in a retrospective study, and proved to be safer and have better curative resection rate in early-stage gastroesophageal neoplasia (8). This conclusion was confirmed by the subsequent studies by Bhat et al (15) and Herrero et al (16). In a previous study (n=72), the cap technique with submucosal injection and the ligation technique without submucosa injection were found to be similar with respect to efficacy and safety in endoscopic resections of early-stage esophageal cancers (17).…”
Section: Discussionmentioning
confidence: 81%
“…Malignant melanoma cells can form tumor blood vessels through vasculogenic mimicry (Maniotis et al., 1999; Hess et al., 2007; Bhat et al., 2009; Helfrich and Schadendorf, 2011). However, cells also produce various growth factors to promote tumor angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Aggressive and metastatic melanomas are rich in tumor vasculature (Bhat et al., 2009; Marneros, 2009). Accumulated evidence has indicated that malignant melanoma cells not only produce various angiogenic factors to promote tumor angiogenesis through ingrowth of the tumor’s vasculature from pre‐existing blood vessels, but also directly form tumor vasculature via tumor vasculogenic mimicry, by which tumor cells line up to form functional blood vessels, independent of vascular endothelial cells (Maniotis et al., 1999; Hess et al., 2007; Bhat et al., 2009; Helfrich and Schadendorf, 2011). Thus, vasculogenic melanoma cells and genes may be rational targets for anti‐melanoma therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation